Islamic Diplomacy and the Palestinian Quest for Peace and Independence: An Analytical Perspective - Candra, Rudi; Mubarok, Sofi (Mediasi Journal of International Relations, 2024)
The Israeli occupation of Palestine is a stain and a black mark on the life of inter-state and international relations in this century. Independence for all nations and countries seems like an impossibility; the UN, as an international institution established to create peace and justice for the world's nations, has failed to fulfill its function. The UN Security Council, responsible for maintaining security, has not offered protection to the Palestinian people. Instead, it has permitted Israel to commit massacres and war crimes against countless lives without reprimand or justice. Similarly, countries around the world seem powerless, able only to condemn without the strength to intervene or stop the situation. This article is written as an effort to explore the opportunities and challenges for the Palestinian state in achieving peace and independence within the realm of international diplomacy. The approach used is based on concepts of Islamic diplomacy, whose main objective is to maintain and create peace among different religious communities and humanity as a whole. This research employs a qualitative methodology with direct fieldwork. The researcher traveled to countries adjacent to Palestine and Israel, including Syria, Lebanon, Saudi Arabia, Egypt, and also Indonesia. Although Indonesia is far away, its uniqueness as a predominantly Muslim nation creates an emotional and political affinity with the Palestinian cause. The research results indicate that the primary challenge for Palestinian independence diplomacy is the lack of unity among Arab countries when confronting Israeli and American diplomacy. Most nations prioritize their own national interests over providing direct support for Palestinian diplomacy and independence.